Detecting overly strong preconditions in refactoring engines - Mongiovi, Melina; Gheyi, Rohit; Soares, Gustavo; Ribeiro, Márcio; Borba, Paulo; Teixeira, Leopoldo (IEEE Transactions on Software Engineering, 2018)
Refactoring engines may have overly strong preconditions preventing developers from applying useful transformations. We find that 32 percent of the Eclipse and JRRT test suites are concerned with detecting overly strong preconditions. In general, developers manually write test cases, which is costly and error prone. Our previous technique detects overly strong preconditions using differential testing. However, it needs at least two refactoring engines. In this work, we propose a technique to detect overly strong preconditions in refactoring engines without needing reference implementations. We automatically generate programs and attempt to refactor them. For each rejected transformation, we attempt to apply it again after disabling the preconditions that lead the refactoring engine to reject the transformation. If it applies a behavior preserving transformation, we consider the disabled preconditions overly strong. We evaluate 10 refactorings of Eclipse and JRRT by generating 154,040 programs. We find 15 overly strong preconditions in Eclipse and 15 in JRRT. Our technique detects 11 bugs that our previous technique cannot detect while missing 5 bugs. We evaluate the technique by replacing the programs generated by JDolly with the input programs of Eclipse and JRRT test suites. Our technique detects 14 overly strong preconditions in Eclipse and 4 in JRRT.